“The Secret” by Yuri Andrukhovych: an autobiographical novel in the form of an interview - Dzyk, Roman (Institute of World Literatures SAS, 2023)
This article examines the novel Taiemnytsia. Zamist’ romanu (The Secret. Instead of a novel, 2007) by Yuri Andrukhovych, one of the most famous contemporary Ukrainian writers. It analyzes the expressive autobiographical nature of the author’s entire work, particularly in the context of his previous novels, which positions Taiemnytsia as the final stage in a progressive movement toward the genre of the autobiographical novel. It also examines the central issue of this genre – combining truth and invention, reality and fiction – to establish that combining both elements results in the emergence of a new genre, straddling the boundary between autobiography and novel by using the form of an interview.
Keywords: The Secret; Yuri Andrukhovych; Modern Ukrainian literature; Genre; Autobiographical novel